PENERAPAN UJI MULTIKOLINIERITAS DALAM PENELITIAN MANAJEMEN SUMBER DAYA MANUSIA - Effiyaldi Yaldi; Johni Paul Karolus Pasaribu; Eddy Suratno; Melani Kadar; Gunardi Gunardi; Ronald Naibaho; Selfi Kumara Hati; Vira Aryati Aryati (LPPM Universitas Dinamika Bangsa, 2022)
This study aims to determine and ensure that the instruments used in a study are guaranteed to be free from multicollinearity problems and minimize the level of bias/deviation with the real conditions that occur with the research results. This study uses a questionnaire as an instrument to collect data. Questionnaires were distributed/distributed to the community/households. The data collection technique is random (random). The results of the analysis show that from the variables used, there is no multicollinearity problem between the independent variables. Given the importance of an instrument free from multicollinearity problems, the suggestion for researchers is to use the research instrument that is truly guaranteed to be free from multicollinearity disorders.